Implementation of Patient's Rights Charter: a Report from Ministry of Health and Medical Education, Iran. - A R Parsapoor; P Salari; B Larijani (Iranian Journal of Public Health, 2013)
At the aim of explaining the rights of health care recipients and upgrading ethical observance in the field of treatment-the most important field of health care-, the Patient's Rights Charter was declared by Ministry of Health and Medical Education to all medical universities in September 2009. This paper provides a report of strategic planning for implementation of Patient's Rights Charter and a summary of other projects.